Poly I:C-priming of adipose-derived mesenchymal stromal cells promotes a pro-tumorigenic phenotype in an immunocompetent mouse model of prostate cancer - Rivera-Cruz, Cosette M.; Kumar, Shreya; Figueiredo, Marxa L. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Mesenchymal stromal cells (MSC) are envisioned as a potential cellular vehicle for targeted cancer therapies due to their tumor tropism and immune permissiveness. An obstacle in their use is the duality in their interactions within tumors, rendering them pro-tumorigenic or anti-tumorigenic, in a context dependent manner. MSC preconditioning, or priming, has been proposed as a strategy for directing the effector properties of MSC at tumor sites. Methods: We primed human MSC derived from adipose tissues (ASC), a clinically advantageous MSC source, utilizing toll-like receptor agonists. Subsequently, we explored the consequences in tumor progression and transcriptome upon the interaction of tumor cells with primed or unprimed ASC in an in vivo model of prostate cancer, the second most common cancer and second leading cause of cancer related death in men in the USA. Results and discussion: In the studied model, poly I:C-primed ASC were found to significantly accelerate tumor growth progression. And while unprimed and LPS-primed ASC did not exert a significant effect on tumor growth at the macroscopic level, gene expression analyses suggested that all treatments promoted distinct modulatory effects in the tumor microenvironment, including altered modulation of angiogenesis, and immune response processes. However, the effects resulting from the collective interaction across these processes must be sufficiently skewed in a pro-tumorigenic or anti-tumorigenic direction for evidence of tumor progression modulation to be detectable at the macroscopic level. Our study highlights potential MSC-tumor microenvironment interactions that may be leveraged and should be considered in the development of cancer therapeutics utilizing MSC.